2022
DOI: 10.3389/fpsyg.2022.864116
|View full text |Cite
|
Sign up to set email alerts
|

No Influence of Emotional Faces or Autistic Traits on Gaze-Cueing in General Population

Abstract: The present study addressed the controversial issue of whether autistic traits in the general population are associated with the automatic and fundamental aspects of joint attention through eye gaze. Specifically, we examined whether the degree of autistic traits is associated with the magnitude of reflexive attention orienting in the direction of another’s eye gaze embedded in neutral and emotional (angry, fearful, and happy) faces. The cue stimuli changed gaze direction and facial expressions simultaneously.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
2
2
0
Order By: Relevance
“…It occurs earlier (e.g., it is reliably observed at the SOA of 200 ms) and extends over the SOA of 600 ms in adults [ 69 ]. Consistent with previous studies, it is not consistently found diminished in adults with ASD [ 36 38 ], nor does it demonstrate a clear association with individual autistic traits [ 105 , 106 ]. We speculate that this may be attributed to the influences of other two factors in social attention.…”
Section: Discussionsupporting
confidence: 89%
“…It occurs earlier (e.g., it is reliably observed at the SOA of 200 ms) and extends over the SOA of 600 ms in adults [ 69 ]. Consistent with previous studies, it is not consistently found diminished in adults with ASD [ 36 38 ], nor does it demonstrate a clear association with individual autistic traits [ 105 , 106 ]. We speculate that this may be attributed to the influences of other two factors in social attention.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, individuals with high autistic traits exhibited the capacity to use individual gaze cues to orient their attention, and they were also proficient in following majority social gaze cues in conflicting social scenarios. Despite our discrepancy with certain research findings [ 27 – 29 ], similar findings were reported in another single cue task, where individuals with high and low autistic traits demonstrated comparable abilities in social attention [ 43 , 44 ]. The absence of differences in gaze cue effects between individuals with high and low autistic traits may stem from the possibility that those with high autistic traits employ compensatory non-social strategies during the gaze-cueing task.…”
Section: Discussionsupporting
confidence: 51%
“…First of all, the imbalance in terms of the numerosity between female and male participants. However, many studies in the GCE literature present a gender imbalance, which should be acknowledged (e.g., [27,45,46]) and tested a much smaller sample than the one reported in the present paper [47].…”
Section: Discussionmentioning
confidence: 65%